Transformasi Nilai Karakter dan Religiusitas Peserta Didik Melalui Projek Pembuatan Peras Pejati di SMA Negeri 2 Singaraja - Suwamba Jaya, Gede; Suwindia, I Gede; Miarta Putra, I Nyoman (Jayapangus Press, 2025)
The reinforcement of character and religiosity values is a crucial element in education, particularly in addressing the challenges of globalization that threaten students' spiritual and cultural identity. The Peras Pejati project at SMA Negeri 2 Singaraja represents a contextual strategy grounded in local culture to instill these values. This study aims to describe the process of character and religiosity internalization, explain the educational functions of the project, and identify the contextual learning that emerged. This research employs a descriptive qualitative approach. Primary data were collected through interviews with the project facilitator teachers, students, and the vice principal of curriculum, while secondary data were obtained from relevant books and documents. Informants were selected using purposive sampling. Data collection techniques included participatory observation, in-depth interviews, and documentation. The results indicate that the project facilitates integrative learning through students' active engagement in symbolic, spiritual, and collaborative processes. Character values such as religiosity, cooperation, independence, discipline, and creativity were developed throughout the activities. The educational functions of the project encompass intellectual, social, communicative, spiritual, and practical dimensions. The project also strengthens teacher role-modeling in character education. The conclusion of this study affirms that the Peras Pejati project serves not only as a medium for cultural preservation, but also as a model of character education based on local culture that can be replicated in other schools.